Strategi dalam Meningkatkan Literasi dan Minat Baca Anak Anak Desa Jaranguda melalui Sosialisasi Literasi - Sindi Rahmadani; Raja Gusti Mandari Siregar; Siti Aulia; Ayu Andini; Nurwani Nurwani (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
The reading ability of children in Indonesia, especially in rural areas, remains a very serious problem. Jaranguda Village in Karo Regency is one of the areas facing this challenge due to the lack of facilities, reading habits, and the dominant use of gadgets. This study aims to identify effective strategies to improve literacy and reading interest in children in Jaranguda Village through literacy socialization activities conducted by KKN students. The study used a qualitative descriptive method with observation and documentation techniques of participants and activity implementers. The results showed that the implementation of four main approaches—namely literacy socialization and strengthening, media-based literacy counseling, the application of literacy in public conversations, and the application of literacy in daily activities—had a positive impact on increasing children's interest and reading ability. Children became more enthusiastic about reading, more confident in conveying the content of reading, and began to get used to reading regularly every day. These findings confirm that literacy packaged in an interactive and fun way can create meaningful learning experiences for children. Therefore, activities like this must continue to be developed and implemented sustainably in other villages so that the culture of literacy from an early age can be improved and strengthened.